Leadless pacemaker versus transvenous single-chamber pacemaker therapy: peri-procedural aspects, utilization of medical resources and patient acceptance. (4th May 2021) - Palmisano, Pietro; Guido, Alessandro; Panico, Vincenzo; Chiuri, Maria Domenica; Chiarillo, Marco Valerio; Sergi, Cesario; Ponzetta, Maria Antonietta; Zaccaria, Maria; Accogli, Michele
ABSTRACT: Background: Leadless pacemaker (L-PM) have been developed in order to overcome the lead- and pocket-related complications associated with transvenous pacemaker (T-PM). The impact of L-PM implantation on the utilization of medical resources, patient comfort and therapy acceptance could differ from that of T-PM. Research design and methods: Prospective, single-center study enrolling 243 consecutive patients undergoing PM implantation. Propensity matching for baseline characteristics yielded 77 matched pairs. Procedural data, patient acceptance (assessed by Florida Patient Acceptance Survey, FPAS) and quality of life (QoL) (assessed at the baseline, 1 week, 3 and 6 months) were compared between the two groups (L-PM and T-PM). Results: The implantation procedure was longer in L-PM than T-PM patients (42.2±16.3 vs. 28.9±11.9 minutes; p<0.001). L-PM was associated with lower intra- and post-operative pain intensity (all p<0.05), shorter hospitalization (3.2±0.5 vs. 3.5±1.1 days; p=0.034), greater patient acceptance (FPAS score: 58.7±7.1 vs. 40.5±4.1; p<0.001), and better QoL on both physical and mental health scales (all p<0.05). Conclusions: Although L-PM implantation takes longer than T-PM, it is better tolerated and accepted by patients and is associated with a better QoL.